Big impacts from small abstractions: The effects of surface water abstraction on freshwater fish assemblages. Issue 1 (24th October 2019) - Boddy, Nixie C.; Fraley, Kevin M.; Warburton, Helen J.; Jellyman, Phillip G.; Booker, Doug J.; Kelly, Dave; McIntosh, Angus R.
Abstract: Abstractions and diversions are prevalent in river networks worldwide; however, specific mechanisms and measures reflecting changes in functional characteristics of aquatic assemblages in response to flow abstraction have not been well established. In particular, the influence of small takes on fish assemblages is poorly understood. Field surveys and stable‐isotope analyses were used to evaluate the impact of differing levels of flow abstraction on fish assemblage structure, and native–non‐native patterns of coexistence, associated with small surface water abstractions in four streams in New Zealand. Study design accounted for longitudinal processes (spatial autocorrelation) to isolate the effects of abstractions on fish assemblages. Reaches with reduced flows downstream of abstraction points had significantly lower fish abundances per metre of stream length, probably because of decreased habitat size, altered interspecific interactions and barriers to movement. The loss of larger fish in reaches with high abstraction resulted in shallower mass–abundance slopes and shorter stable isotope‐derived food‐chain lengths, likely to have been caused by fewer trophic links in the food web. The large fish absent from these reaches were flow‐sensitive introduced salmonids, resulting in higher relative abundances of small‐bodied native fish, probably as a result of predatory and competitive release. Quantification of metrics designed to characterize ecosystem functioning as well as abundance and species composition indicated that small water abstractions can alter both the structure and composition of stream fish assemblages and modify the outcomes of native–non‐native species interactions. Thus, a better understanding of the effects of small abstractions could be used to improve the strategic management of fish in invaded riverscapes.